Sağlık kurumlarında kurumsal performans yönetimi: Üçüncü basamak sağlık hizmeti veren iki hastane için karşılaştırmalı bir analiz - Hanağası, Sena (İstanbul Medipol Üniversitesi Sağlık Bilimleri Enstitüsü, 2021)
Günümüz iş ortamında yöneticilerin kurumlarının performansını artırmak için rekabetçi iş ortamında baskı altında çalışmaktadırlar. Araştırmamız çalışanların örgütsel bağlılığı, iş tatmini ve algılanan kurumsal performans düzeyleri arasındaki farklılıklarını göstermektir. Çalışmanın amacı üçüncü basamak sağlık hizmeti veren MMÜH ve MÇÜH idari personellerinin örgütsel bağlılık, iş tatmini ve algılanan kurumsal performans düzeyleri arasındaki farklılıkları araştırmaktır. Araştırmanın örneklemi Medipol MEGA ve Medipol Üniversitesi Çamlıca Hastanesi idari personelleri oluşturmaktadır. Örgütsel bağlılık ölçeğinin Cronbach's Alpha değeri; 0,71; iş tatmini ölçeğinin Cronbach's Alpha değeri 0,92; algılanan kurumsal performans ölçeğinin Cronbach's Alpha değeri ise 0,90 olarak bulunmuştur. Araştırmada kullanılan üç ölçeğin de güvenilirliği yüksek düzeydedir. Üç ölçeğin de karma değerine bakıldığında ise Cronbach's Alpha değeri 0,93'tür. Katılım gösteren idari personelin %61,6'sının (n=251) MMÜH'nde, %27,6'sının (n=113) ise MÇÜH'nde görev yaptığı görülmektedir. MMÜH'nde çalışan personelin örgütsel bağlılık ortalamaları (X?=3,165, Ss=,476) ve MÇÜH'nde çalışan personelin örgütsel bağlılık ortalamalarından (X?=3,251, Ss=,514; t=-1,60, p>0,05) farklı olmadığı tespit edilmiştir. Örgütsel bağlılık düzeyleri ortalamaları arasında anlamlı bir farklılık yoktur. MMÜH'nde çalışan personelin algılanan kurumsal performans ortalamaları (X?=3,37, Ss=,774) ve MÇÜH'nde çalışan personelin algılanan kurumsal performans ortalamalarından (X?=3,547, Ss=,606; t=-2,32, p<0,05) farklı olduğu tespit edilmiştir. Algılanan performans düzeyleri ortalamaları arasında anlamlı bir farklılık vardır.

In today's business environment, managers work under pressure in a competitive business environment to increase the performance of their institutions. Our research is to show the differences between employees' organizational commitment, job satisfaction and perceived organizational performance levels. The aim of the study is to investigate the differences between the organizational commitment, job satisfaction and perceived institutional performance levels of the administrative staff of MMÜH, which provides tertiary health care, and MÇÜH, which provides tertiary health care. The sample of the research consists of the administrative staff of MMÜH and MÇÜH. The answers given by the administrative staff to the survey questions related to the subject of the research were tested with reliability analysis. Cronbach's Alpha value of organizational commitment scale; 0.71; Cronbach's Alpha value of job satisfaction scale was 0.92; Cronbach's Alpha value of the perceived organizational performance scale was found to be 0.90. The reliability of all three scales used in the research is high. When the mixed value of all three scales is considered, the Cronbach's Alpha value is 0.93. 61.6% (n=251) of the participating administrative staff work at MMÜH, and 27.6% (n=113) at MÇÜH. The organizational commitment averages of the personnel working at MMÜH (X?=3,165, Ss=.476) and the organizational commitment averages of the personnel working at MÇÜH (X?=3,251, Ss=.514; t=-1.60, p>0.05) was not found to be different. There is no significant difference between the mean levels of organizational commitment. Perceived institutional performance averages of the personnel working at MMÜH (X?=3.37, Ss=.774) and the average perceived institutional performance of the personnel working at MÇÜH (X?=3.547, Ss=.606; t=- 2.32, p<0.05) were found to be different.
Corporate performance management in health institutions: A comparative analysis for two hospitals providing third line health care
Keywords: Kurumsal Performans; İş Tatmini; Örgütsel Bağlılık; Üçüncü Basamak Hastane; Performans Yönetimi; Institutional Performance; Job Satisfaction; Organizational Commitment; Tertiary Hospital; Performance Management